Determining Potential Risk Factors for Epilepsy in Children with Neonatal Hypoglycemia: Neonatal Hypoglycemia and Epilepsy Risk Factors - Hosseinzadeh , Shima; Vagharmousavi, Dorsa; Rajabzadeh, Rezvan; Bayani, Ghasem; Babaei, Meisam (Iranian Journal of Child Neurology, 2025)
Objectives: protocols to prevent potential neurological complications are essential. This study aims to investigate the possible risk factors for epilepsy in children with a history of neonatal hypoglycemia in North Khorasan Province. Materials & Methods: This case-control study analyzed 64 children with a previous history of neonatal hypoglycemia between 2017 and 2021 in North Khorasan Province. Nineteen children with epilepsy were selected as the case group, and their MRI data were extracted from medical records. In the control group (45 individuals who did not develop epilepsy), children were randomly selected, and their data were also collected. The researchers completed the ages and stages questionnaire (ASQ) for both case and control groups at follow-up. Pregnancy, delivery, and neonatal health information was obtained from hospital records using a checklist. Statistical analysis was performed using SPSS v20, with data entry and coding accuracy ensured before analysis. Results: This case-control study was conducted on 64 children (19 with epilepsy and 45 without epilepsy) with neonatal hypoglycemia. The mean age for the case and control groups were 4.1 and 4.6 years, respectively. An association was observed between epilepsy prevalence (58%) and familial history (p<0.05). Children who developed epilepsy had more extended periods of hypoglycemia and NICU stays (p<0.05). The age when hypoglycemia starts has a significant impact on the development of epilepsy, with an eight times higher risk for every extra day of life at the time of hypoglycemia (p<0.05). The ASQ findings revealed significant deficiencies between case and control groups (p<0.05). MRI results demonstrated that ~82% of children with epilepsy displayed irregularities, predominantly gliosis, and encephalomalacia in the occipital area (abnormal pathologic findings). Conclusion: Neonatal hypoglycemia significantly raises the likelihood of developing epilepsy in later childhood. This risk is particularly high when the newborn requires an extended stay in the NICU, experiences delayed onset of hypoglycemia, or has a family history of epilepsy. Prompt recognition and focused intervention for newborns with these risk factors are essential to minimize the chances of developing epilepsy and related neurodevelopmental iss